Safety and effectiveness of a novel electric femoral artery compression device for hemostasis after femoral artery puncture - Zhihong Zhong; Hongyang Ni; Xiao Chen; Jun Zhu; Hong Jiang; Jinqing Hu; Dong Lin; Liuguan Bian (Frontiers in Neurology)
ObjectiveThis study aimed to investigate the hemostatic efficacy of a novel electric femoral artery compression device in patients who underwent percutaneous endovascular procedure through femoral artery puncture.MethodsWe retrospectively reviewed 1,086 patients treated with the electric compression device (ECD) and/or vascular closure device (VCD) for hemostasis of femoral catheterization sites. The clinical success of hemostasis and complications of femoral artery puncture site were collected and analyzed.ResultsA total clinical success rate of 84.8% was achieved. Minor complications occurred in 161 of 1,086 patients (14.8%), and major complications occurred in 4 of 1,086 patients (0.4%). Combined application of ECD and VCD showed a lower rate of complications than using ECD or VCD alone in patients who underwent treatment of antiplatelet agents and anticoagulant.ConclusionECD is a safe and effective tool for hemostasis in femoral artery puncture site in percutaneous endovascular procedure with high clinical success and low complication rates.